Bioelectrochemical upgrading of anaerobic digester biogas under thermophilic conditions - Liu Si Ying; Charles Wipa; Cord-Ruwisch Ralf; Cheng Ka Yu; Ho Goen (Renewable Energy and Environmental Sustainability, 2023)
Bioelectrochemical systems (BESs) can be integrated in situ into anaerobic digesters for increasing methane (CH4) content of biogas. Using BES ex situ for improving biogas quality has recently been gaining attention. However, information on the process under thermophilic conditions is very limited. In this study, we placed a BES cathode in-line at the exit gas from a thermophilic anaerobic digester to convert carbon dioxide (CO2) in the biogas into CH4. The performance of the ex situ BES reactor under thermophilic conditions was evaluated. When poising the cathode at −1.1 V versus Ag/AgCl in the ex situ BES reactor, CH4 content increased from 50% to 85%. Of the incoming CO2 73% was biologically converted to CH4 and 23% absorbed by alkalinity generated in the cathode. The energy output as additional CH4 as a percentage of the energy input to operate the BES was calculated at 56%. The biocathode of the BES reactor was dominated by Methanothermobacter spp., which are thermophilic hydrogen consuming methanogens. This study confirms that thermophilic BES can be used as an ex situ treatment process for enriching the CH4 content of biogas. However, energy efficiency of the process was found to be limited by the lack of an energetically efficient anodic reaction. For industrial applications, optimisation of energy efficiency is an area for further research.